Pelatihan Perhitungan Break Even Point dan Target Profit bagi Wirausaha Pemula: Break Even Point and Target Profit Calculation Training for Start-Up Entrepreneurs - Meliza, Meliza (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Weaknesses in managing company finances are one of the reasons why novice entrepreneurs fail to maintain their businesses. Many entrepreneurs still do not understand how to calculate the break-even point (BEP) and profit targets. Therefore, this training aims to improve novice entrepreneurs' understanding and ability to determine the number of break-even points and company profit targets. This training is conducted in four stages, namely identification, socialization, discussion, and evaluation. The results of the training show that there is an increase in participants' understanding of BEP calculations and profit targets. Before the training was held, only 20% of the total participants, or 9 people out of a total of 45 participants understood BEP. Meanwhile, the percentage of participants who knew about calculating profit targets was only 13% of the total participants. After the training was held, the number of participants who understood how to calculate BEP increased to 77% or 35 people. Meanwhile, the percentage of participants who understood how to calculate profit targets increased to 65%.